Gene x environment interactions: Polygenic scores and the impact of a early childhood intervention in Colombia - Orazio P. Attanasio; Gabriella Conti; Pamela Jervis; Costas Meghir; Aysu Okbay (Yale University, Economic Growth Center, 2025)
We evaluate impacts heterogeneity of an Early Childhood Intervention, with respect to the Educational Attainment Polygenic Score (EA4 PGS) constructed from DNA data based on GWAS weights from a European population. We find that the EA4 PGS is predictive of several measures of child development, mother's IQ and, to some extent, educational attainment. We also show that the impacts of the intervention are significantly greater in children with low PGS, to the point that the intervention eliminates the initial genetic disadvantage. Lastly, we find that children with high PGS attract more parental stimulation; however, the latter increases more strongly in children with low PGS.
Keywords: C21; J13; I24; 330; GxE interactions; Early Childhood Development; Stimulation Programs